Towards a Pentecostal Eschatology : Discerning the Way Forward - McQueen, Larry R., (Journal of Pentecostal Theology Supplement Series, 2012)
Growing out of the need to articulate an eschatology that is consistent with the theological beliefs, spiritual experience, and hermeneutical insights of the Pentecostal movement, Toward a Pentecostal Eschatology applies an interdisciplinary approach to the subject, integrating historical, biblical, and theological studies. After providing a comprehensive review of the current state of Pentecostal eschatology, the study explores the periodical literature of the earliest years of the movement, understanding this period to be the heart or originating source of the tradition. Drawing upon insights gained from this exploration, the boundaries for discerning a contemporary Pentecostal eschatology are established and a constructive, biblical-theological contribution to this subject is offered, focused upon a fresh reading of Revelation 21-22 and framed around the narrative testimony of the fivefold gospel that emerges from the heart of the tradition.